Implementation of Inclusive Islamic Education for Children with Special Needs - Nnatu Agatha Ujunwa (Aafiyah: Jurnal Multidisiplin Ilmu, 2025)
Inclusive education has become an important approach in ensuring equal educational opportunities for all children, including children with special needs. In the context of Islamic education, inclusivity reflects Islamic values emphasizing justice, compassion, equality, and respect for human dignity. This study aims to examine the implementation of inclusive Islamic education for children with special needs and analyze its relevance within contemporary educational contexts. The research employs a qualitative descriptive approach through literature review and contextual analysis of inclusive education, Islamic educational philosophy, and special needs learning practices. The findings indicate that inclusive Islamic education contributes positively to the cognitive, social, emotional, and spiritual development of children with special needs by providing accessible, supportive, and non-discriminatory learning environments. Islamic teachings encourage equal treatment, empathy, and social responsibility toward all individuals regardless of physical, intellectual, or social differences. However, the implementation of inclusive Islamic education still faces several challenges, including limited teacher competence, inadequate educational facilities, lack of adaptive learning methods, and social stigma toward children with disabilities. The study emphasizes that collaboration among educational institutions, families, communities, and government agencies is necessary to strengthen inclusive Islamic educational practices. Therefore, implementing inclusive Islamic education based on Islamic ethical values is essential for promoting educational equity, social inclusion, and holistic development for children with special needs in contemporary society.